A vitrifying structure transition in the Dy/Mo(112) adsorption system: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Fedorus, A.; Koval, V.; Naumovets, A.; Pfnür, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Annealing-driven irreversible structural transitions are studied by low energy electron diffraction in submonolayer Dy films adsorbed on the Mo(112) surface. In a wide coverage range q > 0.07, Dy overlayers deposited at low temperatures (T≈ 100 K) are ordered and keep their structure upon annealing up to 350-600 K. Near q = 0.68, the overlayers are stable to high-temperature annealing (Ta = 1000 K) as well, whereas the denser films are metastable and transform to more stable ordered structures. An unusual annealing effect is found for q < 0.58: the initially ordered metastable phases are replaced by phases having no extended order, which are assumed to be two-dimensional glasses.